2018
DOI: 10.1136/vr.k413
|View full text |Cite
|
Sign up to set email alerts
|

How to treatPseudomonasotitis in dogs

Abstract: EVIDENCE IN PRACTICE cases, there is a mixed infection so coccoid bacteria and/or Malassezia may be seen, but Pseudomonas is the critical organism. Otoscopy This can be very challenging to perform in conscious patients. Oten sedation or anaesthesia is required. It may be diicult to view the tympanic membrane. Culture and sensitivity Swabs should be sent for culture and sensitivity in all cases of Pseudomonas otitis. The sensitivity results may not be relevant when using topical treatments because the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Pseudomonas spp., 11,8% (83/702) e P. mirabilis 9,8% (69/702) foram os agentes bacterianos gram-negativos mais frequentes. Estes patógenos, de origem comumente hídrica, estão frequentemente associados à otites crônicas em cães (24). Em estudo similar, Oliveira et al (25) observaram que o segundo agente mais isolado foi P. aeruginosa, mais frequente em infecções polimicrobianas.…”
Section: Resultsunclassified
“…Pseudomonas spp., 11,8% (83/702) e P. mirabilis 9,8% (69/702) foram os agentes bacterianos gram-negativos mais frequentes. Estes patógenos, de origem comumente hídrica, estão frequentemente associados à otites crônicas em cães (24). Em estudo similar, Oliveira et al (25) observaram que o segundo agente mais isolado foi P. aeruginosa, mais frequente em infecções polimicrobianas.…”
Section: Resultsunclassified
“…These findings corroborated a report from Egypt that found 20% P. aeruginosa isolates from canine ear infections. Additionally, P. aeruginosa resistance to b-lactam antibiotics complicates the treatment of P. aeruginosa infection (Al-Charrakh et al, 2016;Cavallo et al, 2000;Barnard and Foster 2018;KuKanich et al, 2022;Okonkwo and Achilike, 2022). According to Morales-Espinosa et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…There are little data on treatment failure in animals; however, a paper by Hawkins et al (2010) on a novel therapeutic reported inclusion criteria for dogs with otitis of at least 3 months with at least three failed antibiotic treatments and therefore suggests treatment failure is an issue. Effective treatments can be challenging and reoccurrence of infection following the cessation of treatment has been reported (Barnard and Foster, 2018). A study on 20 dogs with pyoderma caused by P. aeruginosa , one dog (5%) displayed treatment failure.…”
Section: Assessmentmentioning
confidence: 99%
“…A study on 20 dogs with pyoderma caused by P. aeruginosa , one dog (5%) displayed treatment failure. The remaining dogs were treated for between 3 and 12 weeks and showed resolution of infection (Barnard and Foster, 2018).…”
Section: Assessmentmentioning
confidence: 99%